Optimizing PD-type fuzzy logic controller for position control of spherical robot - Kamis, Nurul Nafisah; Embong, Abd Halim; Ahmad, Salmiah (IEEE, 2020)
Spherical robot has several advantages compared to another type of mobile robot that can be used in many applications. Controlling a rolling mechanism for this nonlinear system is highly challenging. This paper describes the optimization of the position control of spherical robot for rolling mechanism. Proportional-Derivative type Fuzzy Logic Control (PD-type FLC) has been proposed in this paper to control the position of spherical robot while rolling. Five triangular membership function of error, change of error and output voltage is designed, producing 25 rule-base using Mamdani fuzzy inference system. Then, Particle Swarm Optimization (PSO) technique is used to optimize both input and output gain of PD-type FLC. The final analysis of the optimized PD-type FLC has shown that the rise time and settling time of the spherical robot to achieve its desired position is reduced by 78% which is 1.2 min and 2.1 min respectively with no overshoot.